Digitalization and Community Involvement in Qurban Worship in the Modern Era: A Case Study at Jogokariyan Mosque in Yogyakarta - Amalina, Zerin; Alifandi, Mustiadi Gafar; Rasip, Osman Md (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
The development of digital technology has transformed how religious institutions manage worship and engage communities. This study explores the digitalization of qurban worship at the Jogokariyan Mosque in Yogyakarta as a model of adaptive religious practice in the modern era. The research aims to explain the forms of digital technology applied and analyze its impact on community participation and religious awareness. Using a qualitative descriptive method with a field research approach, data were collected through observation, interviews, and documentation. The analysis employed Stig Hjarvard’s theory of the mediatization of religion to interpret how media reshapes religious practices and meanings. The results show that the implementation of online registration, digital payment systems, and real-time qurban reporting successfully increased transparency, efficiency, and trust between mosque administrators and congregants. Moreover, digitalization strengtheed social solidarity and expanded the scope of religious participation across generations and regions. The findings indicate that technology functions not only as an administrative tool but also as a medium for enhancing spiritual experience and social involvement. In conclusion, qurban digitalization at the Jogokariyan Mosque represents an integration of faith, technology, and community engagement, reaffirming the mosque’s role as a center for religious, social, and digital transformation.